MEDIA SOSIAL: PLATFORMISASI DAN BUDAYA KONVERGENSI - Rosaliza, Mita; Risdayati, Risdayati; Syamsidar, Raja (Universitas Lancang Kuning, 2021)
When new technology is available on various platforms, there are many transfers of knowledge content or even the platform itself as a medium that produces culture, the result can be convergence, culture becomes more similar, more similar and uniform as a result, or divergence when culture adopts technology. in a different way that maintains or even accentuates the difference. Johnston and Johal (1999) stated that the internet is a virtual culture by using the dimensions of Hofstede (1980) it can be concluded that internet culture develops and is unified and uniformized. In this case, the algorithm plays a role in regulating the flow of culture that will be transferred to users so that it becomes uniform. Marcus and Gould (2000) review selected platforms for transferring convergent cultures, based on an analysis of the recent work by Hofstede (1991). it can be concluded that culture, as revealed by Hofstede's dimension, does indeed affect multiple platforms and has the potential to be the same or monoculture. With discourse analysis supported by digital data from the Tik Tok platform, this article is expected to contribute to the idea that many platforms are used in social media, which can produce new cultures or even reproduce cultures that are uniform and certain.